Draft genome of the Arabidopsis thaliana phyllosphere bacterium, Williamsia sp. ARP1. Issue 1 (December 2016) - Horn, Hannes; Keller, Alexander; Hildebrandt, Ulrich; Kämpfer, Peter; Riederer, Markus; Hentschel, Ute
Abstract The Gram-positive actinomyceteWilliamsia sp. ARP1 was originally isolated from theArabidopsis thaliana phyllosphere. Here we describe the general physiological features of this microorganism together with the draft genome sequence and annotation. The 4, 745, 080 bp long genome contains 4434 protein-coding genes and 70 RNA genes. To our knowledge, this is only the second reported genome from the genusWilliamsia and the first sequenced strain from the phyllosphere. The presented genomic information is interpreted in the context of an adaptation to the phyllosphere habitat.